Management control of music education in the Mykolaiv National Agrarian University - Sharata, N. (Problems of Engineer-Pedagogical Education, 2018)
The article discusses about management control of artistic and aesthetic education as a problem of pedagogy. Today higher education institution designed to form a new generation of Ukrainian intelligentsia - competent, fully developed, creative and responsible for themselves and their actions, able to actively guide the further development of an independent Ukrainian state all acquired knowledge and skills. Mykolayiv State Agrarian University has always sought and seeks to use art to improve the cultural level of students develop their creative abilities and social activity. The purpose of education of students Mykolaiv National Agrarian University - to form fully and harmoniously developed, morally, culturally, professionally and socially competent person, capable to effectively exercise their rights and responsibilities and successfully carry out professional activities. In the new socio-economic conditions of urgent development of such a set of competencies that will provide young people the ability: to be responsible; make joint decisions; regulate conflicts through nonviolent; understand and accept different cultures, religions, languages and national traditions; have new technologies, understand the scope of their application and dissemination; to innovate; adapt to the modern world.